(untitled) (Zaranie Śląskie, 2023)
From the 18th century until the Second World War, Upper Silesia was home to the noble von Garnier family, who originated from Savoy. Initially, their main residence was the castle in Lubliniec and, after its sale, the palace in Turawa. The family divided into several lines, the oldest of which – the descendants of Franz Xavier (1753–1838) – inherited the estate and residences in Turawa. In 1841, the owner of Turawa, Franciszek Serafin, received the Prussian title of count, inherited by primogeniture. Amand (1795–1861) and his descendants moved and settled in the former Russian Empire (now the lands of Ukraine), creating a Russian-Ukrainian line of the family. Three Garnier family members among those serving in the Prussian army received general ranks: Otto (1830–1908), Franz Xavier (1842–1916) and Otto (1859–1947). Several representatives of this family were honoured with high Prussian orders: Red Eagle and Pour le Mérite. The first part of the article presents the most important events and individuals of this family. The genealogies in the second part are presented by line.